The Influence of Coastal Protective Building against Erosion in Sayung Coastal, Demak - Dwi Yuliasari; Suripin Suripin; Denny Nugroho Sugianto (International Conference on Coastal and Delta Areas, 2017)
In 1980, land conversion of mangrove occur in large numbers since the opening of the Causeway. Flooding and Rob have already begun to be felt since the year 1995 and beginning in 2000 has been sinking a Dukuh village near by Bedono. Year 2000 erosion occurred in district Sayung, Demak and in 2013 the large area known erosion area of 400 – 1300 acres along the coastline. To reduce and overcome the damage done by the shore, re-purposed soft structure (conservation) and hard structure (breakwater). The purpose of this research is to know the influence of the building protective coast against erosion. The method used is the quantitative methods i.e. include survey field and numerical modelling methods. Research results in the form of changes in the rate of erosion in Coastal Sayung Keywords: Coastal, Coastal Building, Erosion, Sediment.